2000
DOI: 10.1007/pl00008390
|View full text |Cite
|
Sign up to set email alerts
|

Do recombinant human erythropoietin and iron supplementation increase the risk of retinopathy of prematurity?

Abstract: Comparing a group of infants treated with recombinant erythropoietin and iron supplementation to a group of control infants, no difference was observed concerning the transfusion need. The incidence of retinopathy of prematurity was significantly higher in the treated group. These data need to be confirmed in randomized controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 4 publications
4
78
0
1
Order By: Relevance
“…The association between rEPO and ROP is based on the angiogenic action of rEPO. 13,14 Romagnoli et al 15 reported an increased risk of ROP when administered in week 1 of life. A recent meta-analysis by Ohlson and Aher 10 showed a greater risk for severe ROP in this subgroup, with a relative risk:1.7 (95% CI: 1.1-2.54) and a number needed to harm: 20 (95% CI: 11-100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between rEPO and ROP is based on the angiogenic action of rEPO. 13,14 Romagnoli et al 15 reported an increased risk of ROP when administered in week 1 of life. A recent meta-analysis by Ohlson and Aher 10 showed a greater risk for severe ROP in this subgroup, with a relative risk:1.7 (95% CI: 1.1-2.54) and a number needed to harm: 20 (95% CI: 11-100).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Nevertheless, because of its demonstrated angiogenic activity, 13 several trials have associated the use of rEPO with retinopathy of prematurity (ROP). 14,15 Current meta-analyses have shown greater ROP incidence in VLBW infants who received rEPO before day 8 of life. [10][11][12] The most suitable dosage schedule, based on pharmacokinetic studies, remains unclear because of differences among studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous randomized placebo-controlled studies have not reported significant differences in the incidence of ROP between Epo treated and placebo infants, retrospective reports have postulated that use of Epo may be associated with increased rates of ROP (32)(33)(34)(35). Brown and colleagues reported an association between cumulative doses of Epo and risk for ROP (33); however, the authors were unable to separate the relationship among extreme prematurity, Epo doses, and ROP.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta analysis of these trials showed that neovascular ROP is increased in EPO-treated infants (Ohlsson and Aher, 2006). A few single center studies have linked EPO use to increased incidence of ROP Romagnoli et al, 2000). Collectively, these data suggest that EPO administration during the second phase of ROP may increase neovascularization.…”
Section: Erythropoietin (Epo)-epomentioning
confidence: 99%